The Role of the Endothelin System in the Vascular Dysregulation Involved in Retinitis Pigmentosa - Francesco Saverio Sorrentino; Claudio Bonifazzi; Paolo Perri (Journal of Ophthalmology)
Retinitis pigmentosa is a clinical and genetic group of inherited retinal disorders characterized by alterations of photoreceptors and retinal pigment epithelium leading to a progressive concentric visual field restriction, which may bring about severe central vision impairment. Haemodynamic studies in patients with retinitis pigmentosa have demonstrated ocular blood flow abnormalities both in retina-choroidal and in retroocular vascular system. Moreover, several investigations have studied the augmentation of endothelin-1 plasma levels systemically in the body and locally in the eye. This might account for vasoconstriction and ischemia, typical in vascular dysregulation syndrome, which can be considered an important factor of reduction of the ocular blood flow in subjects affected by retinitis pigmentosa.